2009
DOI: 10.1073/pnas.0810343106
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor function and promoter architecture govern the evolution of bacterial regulons

Abstract: Evolutionary changes in ancestral regulatory circuits can bring about phenotypic differences between related organisms. Studies of regulatory circuits in eukaryotes suggest that these modifications result primarily from changes in cis-regulatory elements (as opposed to alterations in the transcription factors that act upon these sequences). It is presently unclear how the evolution of gene regulatory circuits has proceeded in bacteria, given the rampant effects of horizontal gene transfer, which has significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 47 publications
7
79
0
Order By: Relevance
“…PhoP not only directly regulates the expression of specific genes, including virulence-related ones, but also controls various indirect targets by acting on a set of regulators in Y. pestis (5,15,16). PhoP recognizes the promoter region of rovA to repress its transcription in Y. pestis (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PhoP not only directly regulates the expression of specific genes, including virulence-related ones, but also controls various indirect targets by acting on a set of regulators in Y. pestis (5,15,16). PhoP recognizes the promoter region of rovA to repress its transcription in Y. pestis (19).…”
Section: Discussionmentioning
confidence: 99%
“…CRP senses the switch of catabolites, and glucose may be the only free sugar that the bacteria can detect in hosts, whereas the presence of glucose stops the CRPcAMP machinery (10). Both PhoP and CRP are global regulators controlling complex cellular pathways, including multiple virulence determinants in Y. pestis (5,(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In another study, B. subtilis ComK, which is normally a transcriptional activator, appeared to function mainly as a repressor when it was heterologously expressed in L. lactis (286). Also, by studying PhoP orthologues from Salmonella enterica and Yersinia pestis (79% identical), Perez and Groisman found that they acted differently on promoters (one able and one unable to induce transcription) in the two species even in a case where both orthologues bound the PhoP binding site in the promoter effectively (230). Apparently, the evolution of TF-TFBS interactions involves a complex interplay of both minor modifications to the sequences of TFs and functional changes in the architecture of promoters.…”
Section: Evolution Of Regulatory Networkmentioning
confidence: 99%
“…In both S. enterica serovar Typhimurium and Y. pestis, this property is conferred in part through covalent modification of lipid A phosphate residues with 4-aminoarabinose. Although important divergent regulatory mechanisms exist between genera, 4-aminoarabinose metabolism is controlled by enzymes encoded by ugd and within the pbgP operon (including pmrK) (38). PhoP is a global regulator of gene expression that governs a diversity of transcripts in Y. pestis, including those required for 4-aminoarabinose biosynthesis (15,41,54,56).…”
Section: Identification Of Y Pestis Two-component Gene Regulatory Symentioning
confidence: 99%